In Vitro and In Silico Study of Antibacterial Activity of Sirih Merah Leaf Extract (Piper crocatum Ruiz & Pav.) Against Streptococcus mutans - Yuliana, Trisna; Yusrin, Yolanda Charmenia Nadine; Fauzi, Puad; Aisyah, Lilis Siti; Kurnia, Dikdik (Jurnal Kimia Valensi, 2025)
Sirih merah leaf (Piper crocatum Ruiz & Pav) is a natural material that has the potential to be used as a natural antibacterial agent in treating dental caries caused by Streptococcus mutans because it is known to contain secondary metabolite compounds that have antibacterial properties that can inhibit the activity of glucosyltransferase and glucan-binding protein (Gbp) enzymes produced by S. mutans. This study was conducted to determine the antibacterial activity of Sirih merah leaf extract against S. mutans using the Kirby-Bauer method and to predict the potential molecular activity of antibacterial compounds contained in Sirih merah leaves in inhibiting the growth of S. mutans bacteria in silico using the molecular docking method. Antibacterial activity testing of Sirih merah leaf extract fractions obtained from methanol extract showed that fractions 7 and 10 are active fractions because they can inhibit the growth of S. mutans at the highest concentration of 10% with a strong inhibition zone category. The active fractions were then analyzed by the LC-HRMS method to obtain active compounds. The results of the in silico molecular docking test showed that the active compounds of Sirih merah leaves have the potential to interact with the GtfB and GbpC enzymes of S. mutans, where the best binding energy in the interaction of cafedrine compounds is -8.75 kcal/mol and -9.27 kcal/mol. The docking results were validated through a molecular docking process using native ligands with RMSD values of 1,861 Å and 3,170 Å.